Pneumatosis Intestinalis in a Patient with Acute Promyelocytic Leukemia - Abhishek Mangaonkar; Joshua Mansour; Ryan Keen; Tarun Kukkadapu; Rohini Chintalapally; Vamsi Kota (Case Reports in Hematology)
Pneumatosis Intestinalis is a rare condition characterized by the presence of gas within the intestinal wall. We describe a case of a 33-year-old woman with acute promyelocytic leukemia who developed nausea and nonbloody diarrhea. CT showed intramural air in transverse and descending colon. Patient clinically improved with conservative management.